Analisis Kualitas Website Universitas Musi Rawas Menggunakan Metode Webqual 4.0 - Syafi’ul Hamidani; Darius Antoni; Afriyudi Afriyudi (Jurnal Informatika Global)
ABSTRACTThe Webqual method is one method for testing the quality level of a website based on the perceptions of end users. This method is a development of the Servqual Method that is widely used for measuring service quality. The purpose of this research is  to determine the feasibility of the Musi Rawas University website using WebQual 4.0. Structural equation models (SEM) is used as methods and techniques for data analysis. samples in this study as many as 201 people. The data collection technique using questionnaires. Before the questionnaire distributed tested first using validity and reliability test and assessment with the Likert scale. On the validity of the test using the formula Pearson Bevariate while the reliability test using Cronbach's alpha formula. In the assessment using a Likert scale used 5 ratings interval, is Strongly Agree, Agree, Doubt, Disagree and Strongly Disagree. Based on the results of the test of validity views of rhitung> from 0.138 rtabel value then the question is valid. The results of the analysis of the reliability test rhitung> rtabel value of 0.138. From the results of this study concluded that one of the dimensions of WebQual 4.0, namely the quality of information, does not affect user satisfaction significantly. In other words, the manager of the website should give more attention to providing quality information content. Keywords : Webqual, Validity, ReliabilityABSTRAKMetode Webqual merupakan salah satu metode untuk melakukan pengujian tingkat kualitas website berdasarkan persepsi pengguna akhir, Metode ini merupakan pengembangan dari Metode Servqual yang banyak digunakan untuk pengukuran kualitas jasa. Tujuan dari penelitian ini adalah untuk mengetahui kelayakan website universitas musi rawas dengan menggunakan metode webqual 4.0 dan teknik analisis data menggunakan Structural equation model (SEM). Sampel dalam penelitian ini sebanyak 201 orang mahasiswa. Teknik pengumpulan data dengan menggunakan kuisioner atau angket. Sebelum angket disebarkan diuji terlebih dahulu menggunakan uji validitas dan uji reliabilitas dan penilaian dengan skala likert. Dari hasil penelitian dapat disimpulkan bahwa salah satu dimensi dari WebQual 4.0, yaitu kualitas informasi, tidak mempengaruhi kepuasan pengguna secara signifikan. Dengan kata lain, pengelola website harus memberikan perhatian lebih untuk menyediakan konten informasi yang berkualitas.Kata kunci : Webqual, Validitas, Reliabilitas